2006
DOI: 10.1038/sj.embor.7400823
|View full text |Cite
|
Sign up to set email alerts
|

The UBL domain of PLIC‐1 regulates aggresome formation

Abstract: Defects in protein folding and the proteasomal pathway have been linked with many neurodegenerative diseases. PLIC-1 (protein linking IAP to the cytoskeleton) is a ubiquitin-like protein that binds to the ubiquitin-interacting motif (UIM) of the proteasomal subunit S5a. Here, we show that PLIC-1 also binds to the UIM proteins ataxin 3-a deubiquitinating enzymeHSJ1a-a co-chaperone-and EPS15 (epidermal growth factor substrate 15)-an endocytic protein. Using a polyglutamine (polyQ) disease model, we found that bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 29 publications
3
100
0
Order By: Relevance
“…Specifically, ubiquilin has been shown to protect against polyglutamine-induced toxicity in cellular and invertebrate models of Huntington's disease (60,61). Ubiquilin is also involved in aggresome formation (62) and may promote removal of cellular aggregates via autophagy (63,64). Taken together, our results and those from previous studies suggest that ubiquilin plays an important role in quality control of aggregation-prone cellular proteins.…”
Section: Ubiquilin-1 Is a Molecular Chaperonesupporting
confidence: 79%
“…Specifically, ubiquilin has been shown to protect against polyglutamine-induced toxicity in cellular and invertebrate models of Huntington's disease (60,61). Ubiquilin is also involved in aggresome formation (62) and may promote removal of cellular aggregates via autophagy (63,64). Taken together, our results and those from previous studies suggest that ubiquilin plays an important role in quality control of aggregation-prone cellular proteins.…”
Section: Ubiquilin-1 Is a Molecular Chaperonesupporting
confidence: 79%
“…Previous studies demonstrated that UBQLN forms aggresome-like structures when coexpressed with presenilins or polyglutamine proteins and that UBQLN colocalizes with endosomal and proteasomal markers (34,35,52,53). UBQLN interacts with the S5a subunit of the 19 S proteasome cap in a UBL domain-dependent manner (53,54) and its overexpression results in the accumulation of several proteins, including GABA A , PS1/PS2, p53, amyloid precursor protein, IB␣, and Kaposi sarcoma-associated Herpesvirus protein K7 (52,(55)(56)(57)(58). A general model that has emerged from these studies is that UBQLN and related UBL-UBA domain proteins, such as RAD23, regulate protein homeostasis by guiding ubiquitylated substrates to the proteasome via UBA-polyubiquitin interactions (29,34,36,51).…”
Section: Discussionmentioning
confidence: 99%
“…Aggresomes are induced by various proteins such as ␣-synuclein (Lee and Lee, 2002) and HDAC6 deacetylase in Parkinson's disease (Kawaguchi et al, 2003) and prions in prion-associated disease (Kristiansen et al, 2005). Smaller scattered protein aggregates or aggresome-like structures are detected, for example, with PLIC-1 (Heir et al, 2006) and p62/SQSTM1 (Zatloukal et al, 2002;Paine et al, 2005;Pankiv et al, 2007).…”
Section: Introductionmentioning
confidence: 99%